Cooperatives as institutions for democratization and development the case of Isabel Bay Multi-Purpose Cooperative. - Sydiongco, Jacqueline Carlotta B. (Tacloban City Jacqueline Carlotta B. Sydiongco, 2009)
The cooperative movement in the Philippines has been widespread and unparalleled. Cooperatives are self-help organizations known for their voluntary character and work in popular and economic empowerment. Thus, democratization and development, two facets of the organization, are given much attention in this work. Specifically, this research intends to evaluate the performance of the Isabel Bay Multi-Purpose Cooperative as a vehicle for democratization and development through the following variables: degree of participation of members, financial independence and sustainability, membership benefits and formation of networks and linkages. As a qualitative study, this paper heavily relied on the responses of the cooperative's members and highlighted their stories and experiences on cooperative work and activities. Based on the results of this study, Isabel Bay Multi-Purpose Cooperative has indeed served as an organization which is geared towards development and the promotion of democratization in Isabel, Leyte.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science